Characteristics of clinical trials for non-small cell lung cancer therapeutic vaccines registered on ClinicalTrials.gov - Gu, Wenyue; Xu, Yangjie; Chen, Xiaohong; Jiang, Hao (Frontiers in Immunology, 2022)
Background: Even after complete surgical treatment or chemotherapy, patients with Non-Small Cell Lung Cancer (NSCLC) are also at substantial risk for recurrence and spread trend. Therapeutic cancer vaccination could increase the anti-tumor immune response and prevent tumor relapse. The aim of this study was to assess the characteristics of NSCLC therapeutic vaccines registered on ClinicalTrials.gov. Methods: We conducted a cross-sectional, descriptive study of clinical trials for Non-Small Cell Lung Cancer Therapeutic Vaccines Registered on ClinicalTrials.gov (https://clinicaltrials.gov/) through March 17, 2022. Results: This study encompassed 117 registered trials were included for data analysis. The number of trials was significantly correlated with beginning year (r = 0.504, P < 0.010). Of these trials, 45.30% trials were completed, 12.82% were terminated, and 8.55% were withdrawn. More than half of trials (52.99%) were funded by industry, and more than half of trials (52.14%) located in economically developed North America. Regarding study designs of these trials, 27.35% trials were randomized, 52.14% were a single group assignments, 83.76% were without masking, 35.90% were phase 1, and more than half of the trials (56.41%) recruited less than 50 participants. The highest proportion of vaccine types was protein/peptide vaccines (41.88%). Regarding TNM staging, the highest proportion of the trials is stage III - IV (26.50%). Conclusion: The number of clinic trials about the cancer therapeutic vaccines was sustained increase in recent years. The main characteristic of clinical trials for NSCLC therapeutic vaccines is lack randomized controlled, lack masked, and recruiting less than 50 participants. The protein/peptide vaccines for NSCLC active immunotherapy have been well studied in recent years.